Pengaruh Pendidikan dan Perilaku Keagamaan terhadap Penggunaan Lembaga Keuangan Syariah (Studi Kasus di Desa Banjarwati Kecamatan Paciran Kabupaten Lamongan) - Risma Damayanti; R. Zainul Musthofa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The lack of public understanding of the products and services offered by Islamic financial institutions makes most people only see that the added value of Islamic financial institutions is halal and also aims to help others, many still think that Islamic financial institutions are the same as conventional financial institutions. Banjarwati Village Community is also a village with a Muslim community. This research was conducted in the people of Banjarwati Village, Paciran District, Lamongan Regency, which consisted of 5,825 residents with the aim of: to find out whether educational factors and religious behavior influence the use of Islamic financial institutions in the people of Banjarwati Village, Paciran District, Lamongan Regency. The number of respondents was 80 respondents. The sample collection technique uses the Simple Random Sampling method. Multiple Linear Regression analysis technique with SPSS 16.0 computer program. The results of this study show that partially the significance value of the education variable is 0.000 > 0.05 and the t count is 6.845 > t table 1.991 meaning that the education variable influences the use of Islamic financial institutions. Partially, the significance value of the religious behavior variable is 0.088 > 0.05 and the t count is 1.726 <t table 1.991 meaning that there is no influence from the religious behavior variable on the use of Islamic financial institutions. Simultaneously the calculated F value is greater than F table (31.130 > 3.106) and the significance value is α = 0.05 (0.000 <0.05) meaning that the variables of education and religious behavior together have a significant effect on the use of Islamic financial institutions.